Core stability: How can it be assessed? - Cholewicki, J.; Reeves, N.; Popovich, J.; Priess, M.; Choi, J.; Radcliffe, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: There is ample evidence that fit motor control and core stability are essential for avoiding injuries in high-level athletic performances (Cholewicki et al. 2005; Zazulak et al. 2007). A variety of methods have been developed to assess core stability, such as balance performance and trunk response to random perturbations (Borghuis et al. 2008). While these methods quantify performance in a specific task, they are generally not suitable for assessing system`s control in response to a variety of inputs. Therefore, we developed a systems engineering-based method for assessing trunk motor control using position and force tracking and stabilization tasks. Methods: Tracking tasks involved following a time-varying input signal displayed on a screen by changing the sagittal trunk angle with respect to the pelvis (position tracking) or by changing force exerted with the trunk against a force transducer (force tracking). Stabilization tasks involved maintaining a constant trunk angular position (position stabilization) or constant trunk force (force stabilization) while a sagittal plane disturbance input was applied to the pelvis using a robotic platform. Ten healthy subjects performed six tasks on two separate days: trunk position tracking and stabilization in the sagittal plane, and force tracking and stabilization in trunk flexion and extension. Additionally, ten subjects with low back pain (LBP) also executed this battery of tests to determine their feasibility. Error for each task was computed in time and frequency domains (root mean square and H2 norm, respectively). Intra-class correlation coefficients (ICC) for error and coefficients of multiple correlations (CMC) for frequency response curves were used to quantify reliability of each task. Results: Reliability coefficients (intraclass correlation coefficient (ICC) and coefficient of multiple correlations (CMC)) for all tasks were excellent (between-day ICC . 0.80 and CMC . 0.75, within-day CMC . 0.85). LBP did not significantly increase immediately or 1-3 days after the testing session(s) in any of our participants. Discussion: Position and force control tasks used for assessing trunk motor control appear to be reliable and safe.